Investigating The Relationship Between Teacher Self-Efficacy and Student Achievement - Syarifah; Masuwd, Mowafg; Paisun Paisun (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
In the context of teaching, teacher self-efficacy can significantly impact teaching practices, classroom management strategies, and, ultimately, student learning outcomes. As the educational landscape continues to change rapidly, teachers must prioritize their professional development to meet the diverse needs of their students and ensure their success in the digital age. This study aims to analyze the relationship between teacher self-efficacy and student learning outcomes, teachers, and significant findings or patterns between the two, and compare the results with similar studies from previous studies. A qualitative descriptive method was used in this investigation, using a case study type. Qualitative descriptive analysis techniques were used for the data analysis process involving 38 teachers, madrasah principals, and K.K.M. Prigen Pasuruan administrators. The results of this study found 1. A positive correlation between teacher self-efficacy and student learning outcomes which highlights the importance of supporting teachers in developing confidence in their self-efficacy. 2. Implications for differences in levels of self-efficacy in various teacher demographic groups such as age, gender, teaching experience, and educational background. 3. Addressing gaps through appropriate interventions and support systems such as appropriate policies, infrastructure and teaching facilities can help strengthen the relationship between teacher independence and student learning outcomes, leading to more effective educational practices and policies in madrasahs and beyond.